Targeted inhibition of activated protein C by a non-active-site inhibitory antibody to treat hemophilia - Xiao-Yan Zhao (Nature Portfolio, 2020)
Activated protein C (APC) is a plasma serine protease with antithrombotic and cytoprotective functions. Here, the authors develop a monoclonal antibody that specifically inhibits APC’s anticoagulant function without compromising its cytoprotective function, and shows efficacy in animal models.